IMPLEMENTATION OF THE EUROPEAN EXPERIENCE OF SOCIAL INCLUSION IN THE TRAINING OF SPECIALISTS OF A SOCIO-ECONOMIC PROFILE (UKRAINIAN CONTEXT) - Demchenko, Olena; Kronivets, Tatyana; Pylypenko, Yaroslava; Khilya, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
In the presented research we briefly outlined the issues of training specialists of socio-economic profile in higher educational institutions of Ukraine. We addressed certain aspects of social inclusion and the key indicators of social inclusion in accordance with the priorities of social policy development in Europe. In particular, the indicators and goals of social inclusion, such as inclusion and/or exclusion of some groups of population, the impact of the level of «poverty» on these processes. And also, the influence of these factors on the educational process in higher education institutions, the formation of empathy, stress resistance, social adaptation, professional and inclusive competence.As a part of our research, we diagnosed the level of empathy (Yusupov, 2002), stress resistance and social adaptation (Holmes & Rage, 2009), social frustration (Wasserman, 2009) of student youth who are included in project activities and studying in basic educational programs. Comparison of statistical data of EU countries and Ukraine on the indicators of inclusion of persons in need of inclusive education in active social processes has been carried out.The analysis briefly presents pedagogical technologies with high efficiency in the formation of competencies of future specialists of socio-economic profile and presents the main trends in the formation of the environment of social inclusion, which are proposed and implemented in the framework of project activities and cooperation with EU countries on the territory of Ukraine.